A broadband infrared radiative transfer scheme including the effect related to vertically inhomogeneous microphysical properties inside water clouds. (July 2022) - Shi, Yi-Ning; Li, Wenwen; Wu, Kun; Zhang, Feng; Chen, Qi
Highlights: A broadband infrared radiative transfer (IRT) scheme is proposed to handle the effect related to vertically inhomogeneous microphysical properties. In the scheme, the exponential expression is introduced to describe vertically inhomogeneous optical properties. The nonlinear IRT equation is solved by coupling perturbation method and two-stream discrete ordinate method. The adding method is applied to handle multiple layer IRT. By applying the proposed scheme into the radiative transfer model of CanAM4, we find that it can reduce the bias caused by ignoring the vertical inhomogeneity of microphysical properties, especially in the upward flux and heating rate calculation. From a perspective of computational time, the proposed IRT scheme takes approximately double time of the conventional scheme when being applied to the radiative transfer model. Abstract: Clouds play an important role in the Earth-atmosphere system. Due to the condensation of water vapour inside clouds, liquid water content and droplet radius vertically increase. It leads to the vertical inhomogeneity of cloud optical properties. However, current climate models divide clouds into a few or several dozen vertically homogeneous layers and ignore this important character. In order to handle the vertical inhomogeneity of cloud optical properties, a broadband infrared radiative transfer (IRT) scheme is proposed in this study. In the scheme, we use exponential expressions to describe vertically inhomogeneous optical properties and handle IRT by combining the perturbation method, the two-stream discrete ordinate method and the adding method. The accuracy of the proposed IRT scheme is evaluated in an idealized single layer case. We also apply the proposed scheme into the radiative transfer model which is used in CanAM4 to simulate IRT in two cloudy atmospheric profiles. By comparing to the benchmark scheme, we find that ignoring the effect related to vertically inhomogeneous microphysical properties of clouds has little impact on the downward flux calculation. However, it causes a bias of 2.53 W/m 2 at cloud top and a bias of 1.51 W/m 2 at the top of the atmosphere in the upward flux calculation. The proposed IRT scheme can reduce these biases to -0.23 W/m 2 and -0.004 W/m 2 . Similar results are also shown in the heating rate calculation. From a perspective of computational time, the proposed IRT scheme is four times more expensive as compared to the conventional two-stream discrete ordinate scheme when considering scheme itself. When we apply both schemes to the radiative transfer model, the proposed IRT scheme takes approximately double time of the conventional scheme. All results show that the proposed IRT scheme is accurate and provide a solution to take cloud's vertical inhomogeneity into account in the climate simulation.